Cobalt metalloid and polybenzoxazine derived composites for bifunctional oxygen electrocatalysis. (20th February 2019) - Barwe, Stefan; Andronescu, Corina; Engels, Ruben; Conzuelo, Felipe; Seisel, Sabine; Wilde, Patrick; Chen, Yen-Ting; Masa, Justus; Schuhmann, Wolfgang
Abstract: The development of bifunctional oxygen electrodes is a key factor for the envisaged application of rechargeable metal-air batteries. In this work, we present a simple procedure based on pyrolysis of polybenzoxazine/metal metalloid nanoparticles composites into efficient bifunctional oxygen reduction and oxygen evolution electrocatalysts. This procedure generates nitrogen-doped carbon with embedded metal metalloid nanoparticles exhibiting high activity towards both, oxygen reduction and oxygen evolution, in 0.1 M KOH with a roundtrip voltage of as low as 0.81 V. Koutecký-Levich analysis coupled with scanning electrochemical microscopy reveals that oxygen is preferentially reduced in a 4e − transfer pathway to hydroxide rather than to hydrogen peroxide. Furthermore, the polybenzoxazine derived carbon matrix allows for stable catalyst fixation on the electrode surface, resulting in unattenuated activity during continuous alternate polarisation between oxygen evolution at 10 mA cm −2 and oxygen reduction at −1.0 mA cm −2 . Graphical abstract: Image 1 Highlights: Bifunctional water splitting catalysts were activated for the ORR by embedment in nitrogen-doped carbon. Direct preparation of Cox B/NC and Cox P/NC on the electrode surface obviates the use of non-conductive organic binders. Cox B/NC and Cox P/NC showed good performance for both reactions preferentially reducing O2 to OH − .